The Effect of Organisational Support and Internal Locus of Control on Employee Performance in the Rectorate Office of the Universitas Muhammadiyah Jakarta - Ahmad Fauzi Rohman; Nazifah Husainah; M. Yusuf (BASKARA : Journal of Business and Entrepreneurship, 2026)
This study investigates the impact of Perceived Organisational Support (POS) and Internal Locus of Control (ILoC) on employee performance, with work motivation as a mediating variable. Using a quantitative-associative approach, data were analysed through structural equation modelling (SEM-PLS). Measurement model evaluations confirmed high validity (AVE > 0.5) and reliability (Cronbach’s Alpha and Composite Reliability > 0.7). The findings reveal that both POS and ILoC exert a positive and significant influence on work motivation. Furthermore, while POS and motivation directly drive employee performance, ILoC showed no significant direct effect. Work motivation, notably, does not serve as a mediator between POS and performance. The results underscore POS as the dominant determinant of productivity. Organisations are advised to prioritise supportive institutional policies to optimise performance outcomes.